Protein-Bound Nano-Injectable Suspension: Unveiling the Promises and Challenges - Eknath D. Ahire; Namrata Savaliya; Kalarav V. Makwana; Sagar Salave; Mandeep Kaur Banth; Bhavesh Bhavsar; Dignesh Khunt; Bhupendra G. Prajapati (Applied Nano)
Protein-bound nano-injectable solutions represent a cutting-edge advancement in nanomedicine, offering a versatile platform for precise and controlled drug delivery. By leveraging the biocompatibility and functional versatility of proteins such as albumin, gelatin, and casein, these nano systems enhance drug solubility, prolong circulation time, and improve site-specific targeting, which are particularly beneficial in cancer and inflammatory diseases. This review provides a comprehensive overview of their formulation strategies, physicochemical characteristics, and biological behavior. Emphasis is placed on therapeutic applications, regulatory considerations, fabrication techniques, and the underlying mechanisms of drug–protein interactions. This review also highlights improved pharmacokinetics and reduced systemic toxicity, while also critically addressing challenges like immunogenicity, protein instability, and production scalability. Recent FDA-approved formulations and emerging innovations in precision medicine and theranostics underscore the transformative potential of protein-based nanosuspensions in next-generation drug delivery systems.